A RADIATION DOSIMETRY ASSESSMENT OF WORKERS IN GREEK STYLE ROTISSERIES THAT USE PELLETS CONTAMINATED BY 137Cs AND 90Sr. Issue 3 (26th February 2019) - Lasithiotakis, Michael; Xarchoulakos, Dimitrios C; Potiriadis, Constantinos
Abstract: This work evaluates the 137 Cs and 90 Sr content of wood pellets of the Greek energy market and additionally calculates worker exposure in Greek catering establishments (rotisseries). Wood pellets and ash samples were analysed through high resolution gamma-ray spectroscopy and liquid scintillation. Imported pellets had higher 137 Cs concentrations, especially pellets that were imported in bulk. Greek pellets had very smaller 137 Cs amounts. Despite the high variation in 137 Cs content the 137 Cs exemption levels were not exceeded in any case. However, if an enrichment factor of 300 is assumed, some ashes samples may exceed 13000 Bq/kg. The highest amounts of 90 Sr were measured in ashes from pellets manufactured abroad in 2015, with up to 1060 Bq/kg. A linear regression model of the ratio of 137 Cs to 90 Sr activity followed our data well, and other sets of data partially. A dosimetry assessment of kitchen employees revealed that maximum possible dose intake reached 400 nSv/year.